(untitled) (Research, Society and Development, 2022)
Introduction: There has been a significant increase in cases of violence against women during the period of imposition of social containment measures in several countries, including Brazil, due to the pandemic caused by the new Coronavirus (SARS-CoV-2), which causes the disease COVID-19. Objectives: To know and discuss the impact of strategies to combat violence on women’s mortality. Methodology: This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. , through the following Descriptors in Health Sciences (DeCS): “public policy” and “violence against women”. Combined with each other by the Boolean AND operator. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. Eighteen articles were selected to compose the sample. Results. There are several forms of violence against women, the woman will be supported during the forensic consultations, complaints through protective measures and by the Maria da Penha law. Conclusion: In addition to the existence of public policies of adequacy and coping networks for measures to be taken by health professionals, the nurse is identified as the main player in the care of women in situations of violence, as they are the authorities who have direct contact with the victim.